2012
DOI: 10.1177/1084713812468514
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Use of Hearing Protection by Trumpet Players

Abstract: Although a great many brass players, and trumpet players in particular, successfully use high-fidelity earplugs, others report problems with their use. This article discusses factors that may discourage a brass player from using hearing protection: These include (a) a lack of acclimatization time; (b) a loss of "fortissimo blare" from the aural distortion generated by the 110-to 120-dB SPL produced at the open ear with fortissimo playing; (c) a shallow earmold seal, leading to a large occlusion effect; (d) a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 8 publications
(11 reference statements)
1
10
0
1
Order By: Relevance
“…In contrast to the pipe musicians, brass musicians showed a lack of risk awareness and nearly negligible hearing conservation practices. It is often reported that brass players experience difficulties with earplugs related to occlusion, or the predominance of the musicians' own buzzing and articulation noises produced while playing due to the covering of the ear canal [21,22]. Indeed both the orchestral and band-based brass players in this study reported difficulty with earplugs and poor uptake, providing yet further evidence of the problems faced by brass players.…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…In contrast to the pipe musicians, brass musicians showed a lack of risk awareness and nearly negligible hearing conservation practices. It is often reported that brass players experience difficulties with earplugs related to occlusion, or the predominance of the musicians' own buzzing and articulation noises produced while playing due to the covering of the ear canal [21,22]. Indeed both the orchestral and band-based brass players in this study reported difficulty with earplugs and poor uptake, providing yet further evidence of the problems faced by brass players.…”
Section: Discussionsupporting
confidence: 50%
“…This includes the making of deeply fitting custom-moulded earplugs as discussed and demonstrated by Killion and Chasin [22,23], which significantly reduces the impact of this problem for brass players. Like their orchestral counterparts, brass musicians playing in bands will need to combine well-fitting earplugs with dedicated practice to develop the skill of playing with earplugs [21].…”
Section: Discussionmentioning
confidence: 99%
“…Although musicians have the power and ability to protect themselves from the risks of NIHL, they are not always consciously ready, socially willing or professionally able to reduce their harmful exposure to amplified music, due to the fact that the use of hearing protection can sometimes hinder the quality of performance. [ 19 20 ] Huttunen et al . [ 19 ] found ear plug use low among 15 classical musicians due to hampered listening to their own and to their colleagues’ playing.…”
Section: Introductionmentioning
confidence: 99%
“…The use of musician earplugs by those who play brass instruments has been discussed by Killion (2012).…”
Section: Always Often Sometimes Occasionally Never Totalmentioning
confidence: 99%
“…This is a challenge acknowledged by several investigators (Laitinen, 2005;Mendes et al, 2007;Santoni & Fiorini, 2010;Zander et al, 2008). It is possible that longer adaptation periods would improve outcomes (as suggested by Killion, 2012). Encouraging participants to try a longer adjustment period on the basis of potential improvements over time might motivate participants to maintain earplug use over a longer trial period.…”
Section: Alwaysmentioning
confidence: 99%